Bilingual Unpacking of Monolingual Texts in Two Primary Classrooms in Brunei Darussalam - Martin, Peter W. (Language and education, 1999)
Despite arguments put forward by constructivists, it is acknowledged that teacher talk has remained dominant in the classroom. This is particularly so in the Southeast Asian context where the traditional teacher-centred classroom is the mainstay of educational practice in the school. Most studies on classrooms in developing countries in general, and in Southeast Asia in particular, have been concerned with such issues as the availability and quality of instructional materials, curricular innovations, and the quantity and quality of teachers. Few studies have actually provided in-depth portraits of the classrooms. Consequently, little is known about the interactional patterns in the classroom in multilingual contexts. The present paper reports on empirical research in two fourth-year primary classrooms in Brunei Darussalam, Southeast Asia's newest independent nation. Brunei Darussalam operates a bilingual system of education in which Malay is the language of instruction in the first three years of schooling; in the fourth year there is a switch to English for a number of subjects. The paper highlights the relationship between bilingual talk and monolingual texts, that is, how the monolingual textbook is embedded in bilingual interaction in the classroom.